Small‐volume blood sample collection tubes in adult intensive care units: A rapid practice guideline - Callum, J; Putowski, Z; Alhazzani, W; Belley‐Cote, E; Møller, MH; Curry, N; Al Duhailib, Z; Fung, M; Giocobbo, L; Granholm, A; Louw, V; Maybohm, P; et al. (Wiley, 2024)
Background: This Intensive Care Medicine Rapid Practice Guideline (ICM‐RPG) provides an evidence‐based recommendation to address the question: in adult patients in intensive care units (ICUs), should we use small‐volume or conventional blood collection tubes? Methods: We included 23 panelists in 8 countries and assessed and managed financial and intellectual conflicts of interest. Methodological support was provided by the Guidelines in Intensive Care, Development, and Evaluation (GUIDE) group. We conducted a systematic review, including evidence from observational and randomized studies. Using the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) approach, we evaluated the certainty of evidence and developed recommendations using the Evidence‐to‐Decision framework. Results: We identified 8 studies (1 cluster and 2 patient‐level randomized trials; 5 observational studies) comparing small‐volume to conventional tubes. We had high certainty evidence that small‐volume tubes reduce daily and cumulative blood sampling volume; and moderate certainty evidence that they reduce the risk of transfusion and mean number of red blood cell units transfused, but these estimates were limited by imprecision. We had high certainty that small‐volume tubes have a similar rate of specimens with insufficient quantity. The panel considered that the desirable effects of small‐volume tubes outweigh the undesirable effects, are less wasteful of resources, and are feasible, as demonstrated by successful implementation across multiple countries, although there are upfront implementation costs to validate small‐volume tubes on laboratory instrumentation. Conclusion: This ICM‐RPG panel made a strong recommendation for the use of small‐volume sample collection tubes in adult ICUs based on overall moderate certainty evidence.